A CROSS-SECTIONAL STUDY ON JOB-RELATED LOW BACK PAIN (LBP) ON NURSING STAFF IN TERTIARY CARE HOSPITAL OF KARACHI, SINDH - Rashid Hussain1, Tanseer Ahmed2 , Bahadur Ali3 , Gotam Kumar4 , Imran Ahmed5 , Attiq-urRehman6. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Low back pain (LBP) It is musculoskeletal disorder that exist in various occupation nowadays researchers had been proved through research studies in developed and developing countries that there is association of Low back Pain with occupation. This study will help to enhance productivity of nurses or health care provider that will impact of patient outcome also will support in decreasing medical expenses. This study was planned to determine the frequency of Low Back Pain among hospital nurses. OBJECTIVE: This research study was aimed to determine prevalence of low back pain among nurses working at Tertiary care hospitals in Karachi. DESIGN OF STUDY: Descriptive CrossSectional study. PLACE & DURATION: Dow University of Health Sciences (DHUS) and Civil Hospital Karachi, from May 2019 to August 2019. MATERIALS AND METHODS: This crosssectional study was conducted during May-August 2019 on 324 nurses, working at tertiary care hospitals in Karachi, with minimum qualification of 3 years diploma in nursing, and who had minimum 1 year of working experience. The data collection instrument consisted of a section on demographic information and Nordic Musculoskeletal Disorder Scale. The analysis of data was done through SPSS v21, and Data scrutiny involved in the use of descriptive statistics and chi-square test were used. RESULTS: In this study, 59% participants were male, and 75% having bachelor degree. The lifetime frequency of low back pain was 43.5% whereas 12-month and 1-week frequency of low back pain among nurses was 56.7% and 51.5%, respectively. Pain of mild and moderate intensity was present in 134 (96.4%) nurses. CONCLUSION: The frequency of low back pain was high among nurses working in tertiary care hospitals, in Karachi. However, analytic studies examining trends in Low Back Pain and factors associated with it are needed.